THE INFLUENCE OF ENVIRONMENTAL FACTORS AND SHOPPING STIMULI ON IMPULSE BUYING AT INDOMARET KAUDITAN - Tirayoh, Gleadys (FEB Universitas Sam Ratulangi Manado, 2015)
Increasing consumption of goods and services creates the rapid growth of retail business in Indonesia. As the proof, according to APRINDO, in 2015, Indonesian retail industry experiences 15% growth. Therefore, the objective of this research is to identify the influence of Environmental Factors and Shopping Stimuli on Impulse Buying. This research is a quantitative research, uses questionnaires to collect primary data and uses multiple regressions to analyze the data. The population in this research refers to the consumers of Indomaret Kauditan while sample size in this research is 100 respondents. The results show that Environmental Factors and Shopping Stimuli have significant effect on Impulse Buying simultaneously. Moreover, Environmental Factors and Shopping Stimuli also have significant effect on impulse buying partially. As the recommendation of this research, Indomaret Kauditan is expected to pay attention to the environmental factors such as the parking area, the layout of products, and shopping atmosphere to increase buying intention of shoppers in order to improve Impulse Buying. Keywords: environmental factors, shopping stimuli, impulse buying